TO PROGEJECT MANAGEMENT PROBLEM IN MODERN ECONOMY - Stanislav M. KHASHCHIN; Andrey E. SAFRONOV; Dmitry V. RUDOY; Sergey N. MERZLIKIN (Advanced Engineering Research, 2010)
Questions of project management, current situation in this field, management reforms of the scientific and scientific-technical activities of the Russian government are considered.